A Novel Method for Synthesis of Pyrazolines and Pyrazoles - Tayde, V.B.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Some new 3,5-diaryl pyrazolines and 3,5-diaryl pyrazoles have been synthesized by a novel method by short route. 3,5-Diaryl-1-pyridoyl pyrazolines (4) were synthesized by the reaction of 2-hydroxy acetophenones (1) with isoniazid in alcohol medium containing a little piperidine. 2-hydroxy acetophenones (1) on reacting with phenyl hydrazine hydrochloride in alcohol medium containing a little piperidine produces 3,5-diaryl-1-phenyl pyrazolines (3). 2-Aroyl acetophenones (2) with phenylhydrazine hydrochloride in alcohol medium containing a little piperidine produces 3,5-diaryl-1- phenyl pyrazoles (5). Structures of these compounds have been established by spectral analysis (IR, UV and NMR).